Mengapa Pembaca Berlangganan Majalah Berita? - Priatna, Priatna (Persatuan Wartawan Indonesia, 2019)
Publishing industry is a business that relies on the advertising and circulation. As part of it, the print magazine industryâ€™s total revenue mainly is received from its subscription and retail. Â As the rapid development of online media nowadays, the print magazine company is hit hard. Its revenue were decreased, especially from both revenue sources. On the side of online media, the total revenue is growing significantly. Although the percentage growth is only about 10% at the moment, the figure continues to grow. Although the trend in recent years continues to decline, the print magazine company still depend on its business to generate greater revenue. In the same time, they develops its digital media business. Several theoretical studies and previous research revealed how to maintain the print magazine business. One of it says that publishers should enlarger the number of customers compared to retail buyers, because the growing number of subscribers could give the assurance for its revenue. In the long run, it could bring more power to the company to survive. Â For this reason, this study aims to determine the factors that affect the magazine readers to subscribe. The method used quantitative approach by relying on the survey through questionnaires. The data processing tools were using Excel, SPSS 16 and Structural Equation Model (SEM). The result of this study is, service quality of the magazine publisher become the most dominant factor that attract people to subscribe. Then it followed by customer service quality, physical magazine quality, corporate reputation and brand, price, objectivity and promotion.